If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(a + -3) + 2 = 0 Reorder the terms: 9(-3 + a) + 2 = 0 (-3 * 9 + a * 9) + 2 = 0 (-27 + 9a) + 2 = 0 Reorder the terms: -27 + 2 + 9a = 0 Combine like terms: -27 + 2 = -25 -25 + 9a = 0 Solving -25 + 9a = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '25' to each side of the equation. -25 + 25 + 9a = 0 + 25 Combine like terms: -25 + 25 = 0 0 + 9a = 0 + 25 9a = 0 + 25 Combine like terms: 0 + 25 = 25 9a = 25 Divide each side by '9'. a = 2.777777778 Simplifying a = 2.777777778
| 3.5x-20=2.4x-13 | | -x-x^2=14 | | 2x+4y=76 | | -7x+1=-12x-12 | | -5(1-5k)+5(-8k-2)=-4k-8k | | 12x-3=13x-1 | | 8y=2x | | 100-x=-81 | | 7+q-7q-6q+3= | | 6a-17=4a+1 | | -7(2n-6)=7(n+3) | | 8=z-7 | | 3+9z-8h= | | 7x-8=3(x+2) | | 15x-9x=48 | | 8b-a=-3 | | 4(3d-2)=32 | | x^2+2x-52=0 | | -6(5+3x)=14 | | cos(6x)=cos(4x) | | 14.2=0.4(20m-7.8) | | 24+9=21 | | 24+9= | | a+4b=6 | | 12(2e+3)=96 | | -4z-5=8z+3 | | C=20n+8 | | (2z+9)(7-z)=0 | | f(x)=-8x^2+8x+9 | | y=x^2ln(3x) | | n+33=25 | | y=3*(-3)+10 |